Military spending and global security humanitarian and environmental perspectives - Rufanges, Jordi Calvo (Routledge studies in defence and peace economics, 2021)
Global military expenditure reached an estimated $1,822 billion in 2018 and this book questions what that spending responds to and indeed what that entails in terms of global security.The book draws from prior knowledge and research on military expenditure but introduces an all-encompassing, in-depth and original analysis of military spending as a key and often overlooked factor of global instability, delving into the present and future consequences of its perpetual growth, as well as confronting the reasoning behind it. The authors argue that increasing military expenditure is not the best response to the emergencies militarization itself has helped create. They assert that militarization is paradoxically both a cause of and a response to the grave challenges our society is facing. The book explains why people are not well served by nation-states when they continuously seek to out-compete one another in the size and destructive powers of their militaries. It discusses the scope of military spending around the world, while explaining how militarism is linked with conflict and security threats, and how military spending further prevents us from adequately dealing with global environmental problems like climate change.A must-read for scholars, researchers and students from a wide range of disciplines. It will also find an audience among professionals from the third sector and activists working on issues related to peace, security and militarism, as well as social and climate justice